2018
DOI: 10.1126/scisignal.aal2869
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 adopts three homodimeric conformations that control cell surface delivery

Abstract: Biophysical methods and x-ray crystallography have revealed that class A G protein-coupled receptors (GPCRs) can form homodimers. We combined computational approaches with receptor cross-linking, energy transfer, and a newly developed functional export assay to characterize the residues involved in the dimerization interfaces of the chemokine receptor CCR5, the major co-receptor for HIV-1 entry into cells. We provide evidence of three distinct CCR5 dimeric organizations, involving residues of transmembrane hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 68 publications
6
66
0
Order By: Relevance
“…An additional application of the PALM imaging studies was the integration with molecular modelling approaches to identify possible LHR-LHR interfaces. Surprisingly, this suggested that multiple interfaces for distinct di/oligomers were predicted, and is consistent with the concept that these receptors form diverse physical and functional complexes in our study and more recently in work with distinct Class A GPCRs (25)(26)(27).…”
Section: Pd-palm Unveils Spatial Organization and Stoichiometry Of Gpsupporting
confidence: 92%
“…An additional application of the PALM imaging studies was the integration with molecular modelling approaches to identify possible LHR-LHR interfaces. Surprisingly, this suggested that multiple interfaces for distinct di/oligomers were predicted, and is consistent with the concept that these receptors form diverse physical and functional complexes in our study and more recently in work with distinct Class A GPCRs (25)(26)(27).…”
Section: Pd-palm Unveils Spatial Organization and Stoichiometry Of Gpsupporting
confidence: 92%
“…To investigate the role of CCR5 di-/oligo-merization in gp120 binding, we compared the ligand binding properties of FLAG/SNAP-tagged wild-type (WT) and L196K CCR5. Indeed, we recently identified that Leu-196 is part of the CCR5 dimerization interface [52]. The L196K mutation results in receptor dimers that are less stable and involve alternative dimerization interfaces, as compared to WT CCR5 ([52] and Fig 3B).…”
Section: Resultsmentioning
confidence: 96%
“…Indeed, we recently identified that Leu-196 is part of the CCR5 dimerization interface [52]. The L196K mutation results in receptor dimers that are less stable and involve alternative dimerization interfaces, as compared to WT CCR5 ([52] and Fig 3B). Receptors were expressed in HEK 293 cells and membranes containing similar amounts of either WT- or L196K-CCR5 (Fig 3A) were prepared.…”
Section: Resultsmentioning
confidence: 96%
“…Crystal structures have provided a relevant guide toward the rational design of such mutations in strategic positions. This strategy has proven effective to map the CCR5 dimeric interface, where disulphide crosslinking experiments based on the dimeric interfaces observed in the CXCR4 and m-opioid receptor crystal structures (Jin et al, 2018).…”
Section: Lessons From Chemokine Receptor X-ray Structuresmentioning
confidence: 99%